Consumption Konsumsi dalam Kajian Ekonomi Islam - Dardo, Domo Dwie Harmini (Master of Sharia Economics Program, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
Consumption is defined as a basic form of economic behavior in life. Every living creature must carry out consumption activities including humans. Humans are often referred to as social beings who cannot be denied that they always need other people in their lives. This research is a qualitative descriptive research. The purpose of this research is to interpret and tell data related to the situation that is currently happening, attitudes/views that occur in society, conflicts of 2 or more circumstances, influence on a condition etc. In this qualitative descriptive research, researchers here use literature review to find information through books, magazines, newspapers, and other literature to form a theoretical basis. This research is also to examine written sources such as scientific journals, reference books, literature, encyclopedias, scientific essays, scientific papers and other sources both in written form and in digital format that are relevant and related to the object being studied. As for the object of this research study are texts or writings that describe and explain consumption in the study of Islamic economics. The conclusions from this journal are: In the Islamic concept it is very important to have a division of types of goods or services between what is haram and what is halal. Islam prohibits excessive and redundant consumption, in this case the ethics of human consumption is very high. Humans must be able to distinguish between what is a need and desire, humans must also prioritize self, family and social benefits, humans are prohibited from making lawful what is stipulated as unlawful and forbidding what is already lawful.